TINJAUAN KEAKURATAN KODE TOPOGRAFI KASUS NEOPLASMA DI RUMAH SAKIT BHAYANGKARA SEMARANG - Anita Maharani; Kriswiharsi Kun Saptorini (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Coding is an activity to determine the diagnosis code and action based on the diagnosis and action given by the doctor to the patient carried out by the coder. Determination of neoplasm codes will produce topographic codes that contain the location of neoplasm and morphological codes that show the nature and behavior of neoplasms. Bhayangkara Hospital in Semarang has not implemented a morphological codes so that the code for neoplasm currently only uses topographic codes. This study aims to describe the accuracy of the topographic code of the main diagnosis of neoplasms in Bhayangkara Hospital Semarang. This study was conducted in March 2019 at Bhayangkara Hospital Semarang by observing medical record documents of neoplasm cases and interviews with coding officers. Data processing is done by editing, tabulating, cross check and analizing data. The research shows that there are 50% of topographical code is accurate and 50% topographical code is inaccurate. Inaccuracy of topographical code occurred because there is no policy the implementation of morphological code, because the morphological code does not affect the rates of health services and because the writing of the diagnosis is unreadable. Keyword : Coding neoplasms, topographic codes, accuracy